Desemprego e qualificação profissional em Parauapebas no estado do Pará - SALES, Carla Rafaela Lemos (Universidade Federal do Pará, 2017)
This thesis has as study object the unemployment between the workers who are submitted to professional qualifications processes. It aims to analyze the relation between the unemployed workers growing and the strong presence of transnational company Vale in the Parauapebas municipality. The research was oriented methodologically by the critical-dialectical method in order to go beyond the appearance of the phenomenon, and apprehend how the international, national and regional trends associated with historical and social reality of the region influence the particularity of unemployment and professional qualifications of Parauapebas. Among the conclusions, are highlighted in the three chapters that: the world trends of work reflect the work precarious process, especially informality, employability and the feminization of labor which are the most characteristics found out in the municipality and contribute to increase in unemployment. Thus, are configured speeches and ideological concepts which provide the capital profitability needs. When verifying the repercussions of precarious process in the Amazon, we see the region functionality to the accumulation capital and, for this, they are Amazon peculiarities. Therefore, it is possible to characterize the interviewees’ profile. It is pointed out as one of the main conclusions which the requirements for entry into the labor market are configured intentionally and to individualize the mechanisms of access and permanence to the labor market, because they potentialize competitiveness through selective criteria and ensure the existence of a reserve army of extremely functional labor to capital expansion.